Treatment of parasitic infection using medicinal Plants – Gift of nature - HIBA RIYADH JAMEEL AL-ABODI, (International Journal of Pharma and Bio Sciences, 2019)
The importance of plants is beyond being used as food, fuel and exporting oxygen. Herbal treatment is the oldest methods of treatments. Herbal therapy is the real and effective experience according to recent studies. The use of medicinal plants dates back to about 60,000 years ago when Neanderthals lived in Iraq. Herbal therapy continues to be effective and have a rich comprehensive history even in this developing and advancing world. This article review s some of the medicinal plants viz Peganumharmala Ficusreligiosa, Nigella sativa,Artemisia herba-alba asso , Origanumvulgare ,Camellia sinensis and Menthalongifolia for its reported medicinal studies. The aim of this review is to summarise some of reported medicinal properties of certain important medicinal plants which would help for further research towards clinical studies